Wideband Low-Profile Printed Dipole Antenna Incorporated with Folded Strips and Corner-Cut Parasitic Patches above the Ground Plane - Kedze, Kam Eucharist; Wang, Heesu; Ta, Son Xuat; Park, Ikmo (IEEE Access, 2019)
In this paper, the design of a wideband high-gain low-profile linearly polarized antenna is presented. The design objectives were achieved by encircling a folded strip around a planar radiating element on the top substrate with corner-cut parasitic patches on the bottom substrate placed above the ground plane. A half-wavelength printed dipole utilized as a radiating element was employed to generate linearly polarized radiation. The contributions of the folded strips and parasitic patches are significant factors in enhancing the bandwidth by producing extra resonance and phase compensation. The experiments and full-wave electromagnetic simulations have provided a platform for the analysis, validation, and verification of the antenna design. The antenna structure has the overall dimensions of 120 mm × 120 mm × 16.3 mm (0.69λ o × 0.69 λ o × 0.094 λ o at 1.74 GHz), and it demonstrated satisfactory measured performance characteristics with a -10-dB impedance bandwidth of 1.39-2.09 GHz (40.22%), a broadside gain of 6.1-8.2 dBi, and a radiation efficiency >88% within the impedance bandwidth.
Keywords: Folded strip; Low-profile antennas; Parasitic patch; Planar antennas; Printed dipole; Wide-band; Folded strip; low-profile antenna; parasitic patch; planar antenna; printed dipole; wideband